Peranan KPU Dalam Meningkatkan Partisipasi Pemilih Pemula Pada Penyelenggaraan Pemilihan Presiden Tahun 2024 Dikaji Menurut Undang- Undang Nomor 7 Tahun 2023 Tentang Pemilihan Umum - Agung Fadilah; Muhammad Emir Faisal; Raden Mega Junia Natadikara; Siti Jenar Maharani (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This research aims to analyze the role of the General Election Commission (KPU) in increasing the participation of first-time voters in holding the 2024 General Election. With the role of the KPU, various efforts have been made to increase the participation of first-time voters in the 2024 General Election. This research uses normative juridical research methods, namely research using how to search, review and analyze library sources. This research also uses primary legal material, namely legal material originating from statutory regulations, such as the Undang-Undang Dasar 1945, Undang-Undang Nomor 7 Tahun 2023 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2022 tentang Perubahan atas Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum. Apart from that, this research is also supported by using secondary legal materials such as journals and books that are relevant to this research, as well as using tertiary legal materials in the form of facts and data from the internet. The results of the research show that the participation of first-time voters in the 2024 elections is very influential, in fact the participation of first-time voters will increase compared to 2019. The KPU has made several efforts to increase the participation of first-time voters in the elections, one of which is by providing political education and carrying out various outreach activities to increase awareness of new voters about the importance of elections.